How to optimize the diagnostic yield of endoscopic ultrasound-guided fine-needle sampling in solid pancreatic lesions from a technical perspective - Nam Hee Kim; Hong Joo Kim (International Journal of Gastrointestinal Intervention, 2023)
Endoscopic ultrasound-guided fine-needle aspiration is currently the gold standard in the diagnosis of solid pancreatic lesions, with high diagnostic accuracy. However, this technique is demanding, as its diagnostic yield and efficacy are affected by several factors, including the rapid on-site cytologic evaluation, sampling techniques, needle size and type, use of a stylet, suction techniques, number of needle passes, and novel techniques. This article provides information on up-to-date advances and considerations for maximizing the diagnostic yield of endoscopic ultrasound-guided fine-needle sampling in solid pancreatic lesions, especially from a technical perspective.